2012
DOI: 10.3382/ps.2011-01599
|View full text |Cite
|
Sign up to set email alerts
|

The effects of broiler chicken growth rate on valgus, varus, and tibial dyschondroplasia

Abstract: An experiment was conducted to test the hypothesis that the growth rate of broilers influences their susceptibilities to bone abnormalities, causing major leg problems. Leg angulations, described in the twisted legs syndrome as valgus and bilateral or unilateral varus, were investigated in 2 subpopulations of mixed-sex Arkansas randombred broilers. Valgus angulation was classified as mild (tibia-metatarsus angle between 10 and 25°), intermediate (25-45°), or severe (> 45°). Body weight was measured at hatch an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 22 publications
6
50
0
Order By: Relevance
“…These results of the current study are, therefore, consistent with those of the previous studies. Even though bone breaking strength may not be necessarily decreased with increased BW, fast growing birds may have a higher incidence of tibial dyschondroplasia because of a larger loading weight that they must bear (Shim et al, 2012a). The current results also indicate that high energy diets may improve chicken muscle deposition without equally improving bone quality.…”
Section: Discussionsupporting
confidence: 52%
“…These results of the current study are, therefore, consistent with those of the previous studies. Even though bone breaking strength may not be necessarily decreased with increased BW, fast growing birds may have a higher incidence of tibial dyschondroplasia because of a larger loading weight that they must bear (Shim et al, 2012a). The current results also indicate that high energy diets may improve chicken muscle deposition without equally improving bone quality.…”
Section: Discussionsupporting
confidence: 52%
“…It can also cause membrane damage, bone morphogenic inactivation and inhibit angiogenesis [12,13]. In TD, a large number of the cartilage cell damage is due to the apoptosis process and abnormal protein secretion in the cartilage cells, causing a decrease in the cartilage extracellular matrix degradation rate, which limits the space for bone deposition [14,15]. The cells stop to multiply and endure hypertrophy and apoptosis in tibia bone.…”
Section: Discussionmentioning
confidence: 99%
“…Leach and Nesheim suggested that the TD contributes to the accumulation of cartilage extending from the epiphyseal growth plate into the metaphysis [25]. Thiram causes TD lesions [21] due to mitochondrial injury, membrane damage, inhibition of angiogenesis, and cytotoxic effects [13].…”
Section: Discussionmentioning
confidence: 99%
“…In TD, a large amount of the cartilage cell damage is due to the apoptosis process and abnormal protein secretion in cartilage cells, causing a decrease in the cartilage extracellular matrix degradation rate, which limits the space for bone deposition [12,13]. Currently, research focuses on increasing the growth rate and feed conversion ratio (FCR) of broilers; consequently, poultry bone disease incidence is also increasing in the broiler industry [5,14,15].…”
Section: Introductionmentioning
confidence: 99%